Analiza strukturnih dejavnikov trajnostnega gospodarskega razvoja - Friedl, Peter (Naše gospodarstvo, 2010)
This article defines structural factors, with which it is possible to explain sustainable economic development of chosen pattern of the 34 European countries, using a quantitative method. The results of the research demonstrated that it is most reasonable to assume one common factor in the set of selected indicators. A maximum dependence exists between the variable GDP and other variables, while a number of relatively strong connections exist among other indicators. For both maximum likelihood estimation and principal component analysis, the highest proportions of the variance explained with a common factor were reached for long-term unemployment rate, energy intensity of the economy, and activity rate.
Keywords: Europe; Evropa; gospodarstvo; economy; ekonomski razvoj; sustainable development; trajnostni razvoj; ekonomski kazalci